The Relationship between Environmental Sanitation and the Incidence of Diarrhea in Toddlers - Kriswanto Kriswanto; Siti Musyarofah; Mushidah Mushidah (Global Health Science Group, 2021)
Diarrhea is defecation three or more times in one day with a liquid consistency which is one of the infectious diseases that causes death in infants and toddlers, at the Rowosari II Health Center is one of the areas where the number of diarrhea sufferers has increased from 2018-2020. that is as many as 115 people to 125 people. Factors that influence the incidence of diarrhea in toddlers include clean water sources, latrine ownership facilities, and the type of floor. This study aims to determine the relationship between environmental sanitation and the incidence of diarrhea in children under five in the Rowosari II health center. This type of analytic observational research with a cross-sectional approach, with a questionnaire measuring instrument, processed by univariate and bivariate tests, and chi-square test, if it does not meet the requirements then the fishers exact test. The results of the study on 40 respondents who were the patient population of Rowosari II Health Center, it was found that there was a relationship between clean water sources (Pvalue = 0.029) with the incidence of diarrhea in children under five at Rowosari II Health Center during the last six months, and there was no relationship between latrine ownership facilities (Pvalue). = 1.00) and the type of floor (Pvalue = 0.746) (Odds Ratio 95% CI = 1.160 (0.475–2.830) with the incidence of diarrhea in children under five at the Rowosari II Health Center during the last six months. Parents of children under five are expected to better maintain the hygiene conditions of toddlers as well as the environment and related agencies in order to improve health promotion regarding clean, healthy living behavior and using water sources from PAMSIMAS.